Prediction of flowing bottomhole pressure in gas-condensate wells (2013)
Bottom-hole pressures in gas and condensate wells are frequently measured at a great cost and with operational challenges. On the other hand, most analytical estimation procedures either use trial and error or neglect liquid holdup in condensate wells. Using the mechanical energy balance approach, an approximate model was developed to estimate bottom-hole pressure from wellhead pressures in condensate wells without neglecting liquid holdup. The results show that treating gas condensate like dry gas wells lead to over prediction (10-15%) of flowing bottom-hole pressures, with serious consequences on phase behaviour, reservoir characterization and production management.